The Potential Development of Rammang – Rammang Karst Landscape As An Ecotourism In Maros Regency - Hatibu, Hardiyanti; Hanafie Prasad, Abdul Hallaf; Baharuddin, Ichsan Invanni; Nurfadilah, Nurfadilah; Azhim, Muhamad Ihsan (UNM Geographic Journal, 2018)
This research aims: 1) To know the aspects that support the development of land areas Rammang-rammang Karst Landscape as a tourist area. 2) To find the object that has the potential to be developed in Rammang-rammang karst landscapes. 3) To know the steps taken in the development of ecotourism in the Rammang-rammang karst landscape. Objects in this study are tourists and the public. The data presented in the form of primary data taken from questionnaires " The potential development of  Rammang-rammang  karst  landscape as  an ecotourism in Salenrang  village  Bontoa district   Maros  regency ". Decision informant taken by using accidental sampling and snowball sampling technique. Analysis of the data used is descriptive qualitative analysis and SWOT analysis. The results showed that straregi corresponding development in the karst landscape of business development Rammang-rammang as ecotourism is a strategy Strength - Opportunities. Conclusion Among other aspects that support the development of land areas Rammang-rammang Karst Landscape as ecotourism, namely topography, land use, flora and fauna, the presence of water and rainfall, community activities, job type visitor / tourist, infrastructure and programs government. The object that has the potential to be developed in Rammang-rammang karst landscapes include Stone Forest, Bulu Barakka Cave, Acient  Cave, Bidadari lake, Pute river and Berua Village.